Differential and linear insertion of atrioventricular valves: a useful tool?. (November 2014) - Adriaanse, B. M. E.; Bartelings, M. M.; van Vugt, J. M. G.; Chaoui, R.; Gittenberger‐de Groot, A. C.; Haak, M. C.
ABSTRACT Objective The differential insertion of the atrioventricular valves is the ultrasonographic representation of the more apical attachment of the tricuspid valve to the septum with respect to the mitral valve. A linear insertion is present when both valves form a linear continuum and has been suggested as a marker for atrioventricular septal defects (AVSDs). The objective of this study was to evaluate the anatomical substratum of differential and linear insertions of the atrioventricular valves in normal fetal hearts and fetal hearts with an AVSD. Methods The extent and position of the fibrous skeleton and attachment of the atrioventricular valves to the septum were studied in histological sections of 17 normal hearts and four hearts with an AVSD from 10 + 0 weeks' gestation to 3 days postpartum with various immunohistochemical tissue markers. In addition, spatiotemporal image correlation (STIC) volumes of 10 normal hearts and STIC volumes of eight hearts with an AVSD at 13 + 6 to 35 + 5 weeks' gestation were examined. Results The differential insertion of the atrioventricular valves was visible in normal hearts in the four‐chamber plane immediately beneath the aorta, but nearer the diaphragm a linear insertion was found. In hearts with an AVSD, a linear appearance was observed in the four‐chamber plane immediately beneath the aorta. Towards the diaphragm, however, first a differential insertion and, more caudally, a linear insertion was found. Conclusions Both differential and linear insertions can be found in normal fetal hearts and fetal hearts with AVSD, depending on the plane in which the four‐chamber view is visualized. Therefore, measurement of the differential insertion is likely to be useful only in experienced hands. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.